2016
DOI: 10.1111/jcmm.13009
|View full text |Cite
|
Sign up to set email alerts
|

A promoter polymorphism rs2075824 within IMPA2 gene affecting the transcription activity: possible relationship with schizophrenia

Abstract: Previous studies with biological and genetic evidence indicate that the myo‐inositol monophosphatase 2 (IMPA2) gene may influence schizophrenia. We performed a genetic association study in Han Chinese cohorts. Five single nucleotide polymorphisms within IMPA2 promoter region (rs971363, rs971362, rs2075824, rs111410794 and rs111610121), as well as one (rs45442994, in intron 1) that was positively associated in another study, were selected for genotyping in 1397 patients with schizophrenia and 1285 mentally heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…This monophosphatase is one of the key enzymes in inositol phosphate metabolism and finally convert monophosphate into free inositol through dephosphorylation. IMPA2 is received in many studies to be associated with neuropsychiatric diseases, like schizophrenia 26 , epilepsy 27 , bipolar disorder 11,28,29 , and Huntington's disease 12,30 . Also, IMPA2 inhibition is accepted as the therapeutic mechanism of lithium in bipolar disorders 31 .…”
Section: Discussionmentioning
confidence: 99%
“…This monophosphatase is one of the key enzymes in inositol phosphate metabolism and finally convert monophosphate into free inositol through dephosphorylation. IMPA2 is received in many studies to be associated with neuropsychiatric diseases, like schizophrenia 26 , epilepsy 27 , bipolar disorder 11,28,29 , and Huntington's disease 12,30 . Also, IMPA2 inhibition is accepted as the therapeutic mechanism of lithium in bipolar disorders 31 .…”
Section: Discussionmentioning
confidence: 99%
“…Inositol regulates >712 genes and is involved in many intracellular signaling pathways [21]. Previous studies have suggested that a promoter polymorphism of IMPA2 contributes to the risk of schizophrenia by elevating transcription activity in Han Chinese individuals [22]. Another recent study concluded that a potential association exists between single nucleotide polymorphisms in the IMPA2 gene and increased risk of ischemic stroke [23].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we supposed that rs8075977 may affect PEDF gene transcription instead of the function or stability of PEDF. Given the recent functional researches on loci or diseases (Ohnishi et al 2007;Li et al 2016), SNP rs8075977 may be on the transcription factor binding sites and presumably alters PEDF expression by binding a certain transcription factor. Thus we analyzed rs8075977 using publically available software Haploreg (http://archive.…”
Section: Discussionmentioning
confidence: 99%